Event‐driven fault‐tolerant attitude control of spacecraft with finite‐time disturbance observer under input saturation. (5th January 2023) - Amrr, Syed Muhammad; Saidi, Abdelaziz Salah; Nabi, M.
Abstract: This paper investigates the attitude stabilization problem for a bandwidth‐constrained spacecraft subjected to model uncertainty, external disturbances, actuator faults, and saturated input. The proposed attitude controller is developed by combining the disturbance observer with an event‐trigger technique to provide disturbance attenuation meanwhile respecting the constraint on the wireless control network. The proposed disturbance observer estimates the lumped disturbance within a finite time, and its output is then fed to the composite control law. The presented control scheme relaxes the use of a priori upper bound knowledge of disturbance and resolves the unwinding problem in the quaternion‐based attitude representation. The closed‐loop stability analysis under the proposed algorithm shows the uniformly ultimately bounded convergence of state trajectories. Moreover, the designed event trigger approach avoids the Zeno behavior. The numerical simulation with comparative analysis illustrates the efficacy of the proposed controller in terms of convergence time, steady‐state bound, rate of control update, and energy consumption.